Green Controlling - Resource Oriented Controlling of Enterprises Green Controlling - Ressourcenorientierte Steuerung von Unternehmen - Rackow, Tobias; Schuderer, Peter; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2013)
Summary: The first step of raising energy efficiency potential is to reveal unnecessary energy consumption. Subsequently, it is mandatory to provide a tool for the enterprises that generates transparency through visualization of the companies' energy flux along the production processes. This is where "Green Controlling"comes in place, providing a holistic approach through incorporating energy consumption as a fourth main target dimension - besides time, cost and quality - into the enterprise controlling, hence meeting the factual importance of this KPI.
CRIS-Team Scopus Importer:2023-03-07